Dendrimer nanoparticles for colorectal cancer applications. Issue 6 (23rd January 2020) - Carvalho, M. R.; Reis, R. L.; Oliveira, J. M.
Abstract : Routes of dendrimer synthesis and the stages of possible applicability of dendrimer nanoparticles in the case of colorectal cancer. Abstract : Cancer nanotechnology is a prolific field of research, where nanotools are employed to diagnose and treat cancer with unprecedented precision. Targeted drug delivery is fundamental for more efficient cancer treatments. For this, nanoparticles have been extensively used during the past few years in order to improve the specificity, selectivity and controlled release of drug delivery. It holds potential in minimizing systemic toxicity through the development of functionalized particles for targeted treatment. Among all the type of nanoparticles, dendrimers display several advantages, which make them ideal candidates for improved and targeted drug delivery in cancer research. Dendrimers can transport large amounts of drug into specific areas. In addition, they can be employed for monitoring the progress of the treatment process, with an unprecedented theranostic capability. Special emphasis is given to colorectal cancer and to the preferred employed strategies for producing drug-loaded/functionalized NPs for cancer therapy in the past few years.